2013
DOI: 10.3892/mco.2013.61
|View full text |Cite
|
Sign up to set email alerts
|

Plasma miR-200c and miR-18a as potential biomarkers for the detection of colorectal carcinoma

Abstract: Abstract. It has been demonstrated that there are abundant stable microRNAs (miRNAs) in plasma/serum, which can be detected and are potentially disease-specific. The aim of this study was to investigate whether plasma miR-200c and miR-18a can be used as biomarkers for the detection of colorectal carcinoma (CRC). This study was divided into three parts: i) confirmation of higher miR-200c and miR-18a levels in primary CRC tissues compared to normal colorectal tissues; ii) evaluation of plasma miR-200c and miR-18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 23 publications
2
50
0
2
Order By: Relevance
“…miR-200c is a member of the miR-200 family, which was previously shown to inhibit epithelialto-mesenchymal transition (EMT) by targeting the transcriptional repressor of cadherin 1(CDH1), zinc finger E-box binding homeobox 1 (ZEB1), and survival of motor neuron protein interacting protein 1(SIP1); this suggests that these miRNAs could prevent tumor progression by negatively regulating ZEB transcriptional repressors and consequently maintaining E-cadherin junctions and preventing EMT (Bracken et al, 2008;Gregory et al, 2008;Korpal et al, 2008;Park et al, 2008). Upregulation of miR-200c had been found in several cancers, including ovarian cancer (Iorio et al, 2007;Bendoraite et al, 2010), cervical cancer , bile duct cancer (Meng et al, 2006), nasopharyngeal carcinoma (Zhang et al, 2010), lung cancer (Liu et al, 2012), and colorectal cancer (Zhang et al, 2013;Cristobal et al, 2014), as well as GC (Tang et al, 2013;Song et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-200c is a member of the miR-200 family, which was previously shown to inhibit epithelialto-mesenchymal transition (EMT) by targeting the transcriptional repressor of cadherin 1(CDH1), zinc finger E-box binding homeobox 1 (ZEB1), and survival of motor neuron protein interacting protein 1(SIP1); this suggests that these miRNAs could prevent tumor progression by negatively regulating ZEB transcriptional repressors and consequently maintaining E-cadherin junctions and preventing EMT (Bracken et al, 2008;Gregory et al, 2008;Korpal et al, 2008;Park et al, 2008). Upregulation of miR-200c had been found in several cancers, including ovarian cancer (Iorio et al, 2007;Bendoraite et al, 2010), cervical cancer , bile duct cancer (Meng et al, 2006), nasopharyngeal carcinoma (Zhang et al, 2010), lung cancer (Liu et al, 2012), and colorectal cancer (Zhang et al, 2013;Cristobal et al, 2014), as well as GC (Tang et al, 2013;Song et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Related studies have shown that human serum contains miRNAs and that their expression patterns can potentially be used as clinically diagnostic and prognostic biomarkers of various cancers (Cortez et al, 2009(Cortez et al, , 2012. ) is a member of the miR-200 family, which is overexpressed in several cancers, including ovarian cancer (Iorio et al, 2007;Bendoraite et al, 2010), cervical cancer , bile duct cancer (Meng et al, 2006), nasopharyngeal carcinoma (Zhang et al, 2010), lung cancer (Liu et al, 2012), colorectal cancer (Zhang et al, 2013;Cristobal et al, 2014), and GC as well (Tang et al, 2013;Song et al, 2014). Valladares-Ayerbes et al (2012) found that the miR-200c blood expression levels in GC patients were significantly higher than in normal controls (P = 0.018) and that it has the potential to be a predictor of progression and survival.…”
Section: Introductionmentioning
confidence: 99%
“…MiR‐17‐5p, belonging to the miR‐17‐92 cluster, has been found to be upregulated in various cancer tissues and correlated with advanced disease conditions including colorectal cancer, human breast cancer, lung cancer, pancreatic cancer, and so on, which promotes tumorigenesis, cancer cells proliferation, migration, and invasion via regulating P130, HMG box‐containing protein 1, TGFβ‐2 receptors, and other cancer‐related genes 34, 35, 36, 37. MiR‐18a, another pro‐angiogenic miRNA, is also discovered to be increased in several cancers including breast cancer, esophageal squamous cell carcinoma, and colorectal carcinoma, and it induces cancer cells’ proliferation, invasion, and autophagy through regulating PTEN‐PI3K‐AKT‐mTOR signaling axis and Dicer 32, 38, 39. miR‐20a is also regarded as an oncogene in several cancers such as cervical cancer, non‐small cell lung cancer, and anaplastic thyroid cancer, which raised cancer cells’ proliferation, invasion, and spheroid formation (stem cell ability) via targeting multiple genes including CYLD, ATG7, TIMP2, and LIMK1 40, 41, 42, 43.…”
Section: Discussionmentioning
confidence: 99%
“…The upper chambers of the Transwell ® (Santa Cruz Biotechnology, Inc.) were placed onto a 24-well plate containing 500 µl media with 20% FBS or chemokine (Applygen Technologies, Inc.). Cell suspension (200 µl) was added to the upper chamber of the Transwell ® assembly and incubated at 37˚C in a 5% CO 2 atmosphere for 16 h. The Transwell ® assembly was then washed with PBS twice and fixed with pre-chilled methanol (Invitrogen Life Technologies) at -20˚C for 10 min. The upper chamber of the Transwell ® assembly was washed with PBS twice.…”
Section: Cellmentioning
confidence: 99%
“…Colorectal cancer is one of the most commonly diagnosed types of cancer and is a leading cause of cancer-associated mortality worldwide, particularly among populations in Eastern Asia, Eastern Europe and South America (1,2). Risk factors for colorectal cancer include infection, cigarette smoking, alcohol consumption, diet and genetic variations (3).…”
Section: Introductionmentioning
confidence: 99%